Analog implementation of a rear-end DC-AC inverter for realization of a solar system - Fong, Chee Wai. (2010)
Solar converter topologies are power electronic circuits implemented to recondition the Direct Current (DC) power harnessed from the Photovoltaic (PV) arrays for different uses. In this thesis, the converter changes the power from the PV arrays into an Alternating Current (AC) source that is matching to the utility grid, so that this power generated can be pumped into the grid. Several topologies are possible for this application but this project looks into the performance of a 2-stage converter consisting of a DC-DC Boost Converter cascading a DC-AC Voltage Source Inverter (VSI) via a DC link. The study of the performance will be focusing on the hardware implementation of the converter, thus, most of the work done is designing and building the hardware.